PENGARUH KOPI TERHADAP MEMORI JANGKA PENDEK PADA MAHASISWA PENDIDIKAN DOKTER UNIVERSITAS ABULYATAMA - Khatab Khatab; Sefira Uhya (Jurnal Sains Riset, 2021)
Background Coffee is one of the most potent drinking-related components in it, and it has an effect on the central nervous system so that it improves the performance of the box by stimulating the broadmann area on the prefrontal parts in the area 9, 10,11,12 which plays a role in storing information as referred to as memory the maximum can load thinking ability to store, retain, remember, judge, orient, perception, and pay attention to information received by individuals. Research Objectives Objectives To find out the effect of consuming caffeine-containing drinks on Abulyatama University Medical Education. Method This type of research is truly experimental. The study subjects consisted of 36 people aged 18-24 who were divided into 2 groups, namely 18 respondents drinking coffee ang 18 respondents not drinking coffee. The data measured is the difference in short-term memory scores. The giving a cup of brewed coffee as much 20 grams of coffe powder and 150 liters of water. Data analysis using unpaired "t" test with ? = 0,05. Results The average short term memory points after drinking coffee is 26.9444 greater than the average short memory points that do not drink coffee that is equal to 23.0000 from the independent sample T-test statistical tests show (2- tailed) 0,05 This proves there is a difference between the difference in short-term memory improvement between drinking coffee and not drinking coffee Conclusion Coffee improves short-term memory. Conclusion Coffee improves short-term memory.Keywords: coffee, short term memory